AB0566 Evolution of Xerostomia, Xerophthalmia and Salivary Test of Caries Risk of Primary SjÖgren's Syndrome During Pregnancy. (9th June 2015) - Trujillo, E.; Padron, E.; Exposito, L.; Garcia, M.; Sanchez, H.; Trujillo, M.M.
Abstract : Background: Sjögren's syndrome (SS), one of the most common autoimmune diseases, is a chronic systemic process predominantly affecting women. It is characterized by T lymphocyte infiltration of the exocrine glands. Its hallmarks are oral and ocular dryness due to salivary and lacrimal gland involvement. Saliva plays many important roles in maintaining oral health, including rapidly neutralizing acids, and defending the oral cavity from infection. Objectives: The purpose of this study was to determine the effect of pregnancy on oral and ocular dryness and in salivary test of caries risk of patients with primary SS. Methods: We performed a prospective study throughout pregnancy of 12 outpatients diagnosed with primary SS, at the Department of Rheumatology, University Hospital of the Canary Islands.The following variables were recorded for all patients at first visit and then monthly to the end of pregnancy: – Schirmer test (mm/min). – Resting whole saliva test-WST (mm/min) (Heintze et al) – Oral symptoms questionnaire (Neidermaier 1998) – Dry eye questionnaire -DEQ (Begley et al) We collected saliva all the patients in the first month of pregnancy and the months 3, 6 and 9 to make the caries activity test: – Determination of the saliva buffering capacity (System CRT buffer®) to buffer pH fluctuations. – Alban Test ® (0-4) that measures the ability of saliva to produce acid due to microorganisms that counts. – Contains salivary Lactobacillus (LB) and Streptococci Mutans (MS) closely related to dental caries (System CRT bacterium for LB and MS ®). Results: No significant changes in Schirmer test and WST results were recorded during monthly visits of pregnant patients with primary SS, nor were there any significant changes in the results of the two questionnaires administered (Begley DEQ and Neidermaier oral symptoms questionnaire). Evaluation of the test of activity of caries in patients with SS at months 0, 3, 6 and 9 of pregnancy: Conclusions: Pregnancy does not alter the characteristics of xerophthalmia and xerostomia in primary SS. Salivary tests for identification of caries risk show that the capacity buffer of the saliva of the patients of SSP will decline throughout the pregnancy, as well as the capacity of their saliva to produce acid. The percentage of patients with high microbiological test (counts of LB and SM) SSP is also increased as the pregnancy progresses. Therefore, during the pregnancy of patients with SSP is still more necessary to take extra measures of dietary modification and oral hygiene. Disclosure of Interest: None declared